"The evolution of education in Europe from the Middle Ages to the modern era" (Comprehensive Journal of Science, 2026)
This research examines the development of education in Europe from the Middle Ages to the modern era, highlighting the profound transformations in educational philosophy, institutions, and functions. During the Middle Ages, education was dominated by the Church and characterized by a religious and elitist nature. The Renaissance introduced intellectual openness, restoring the value of human-centered learning and expanding the scope of knowledge. In the modern era, education became a structured institutional system under state supervision, emphasizing mass education, curriculum development, and alignment with scientific and technological progress. The study concludes that the evolution of education in Europe resulted from complex interactions among religious, intellectual, political, and social factors, significantly shaping modern European society.
Keywords: Education, Europe, Middle Ages, Renaissance, Modern education, Church, State, Humanities, Educational development.